1999
DOI: 10.1002/(sici)1521-3935(19990101)200:1<31::aid-macp31>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Phase structures, transition behavior and surface alignment in polymers containing rigid rod-like backbones with flexible side chains, 3. The even-odd effect on phase transitions in combined liquid crystal polyesters

Abstract: SUMMARY: A series of "combined" liquid crystal (LC) polyesters consisting of aromatic main-chain backbones and flexible aliphatic side chains with 4-cyanobiphenyl end groups was synthesized based on the polycondensation of 2,29-bis(trifluoromethyl)-4,49-biphenyldicarbonyl chloride with 2,29-bis{x-[4-(4-cyanophenyl)phenoxy]-n-alkoxycarbonyl]}-4,49-biphenyldiol (PEFBP). In a recent study of PEFBP(n = 11) containing eleven methylene units in the side chains, four different phases were identified in addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…Again, this endothermic process seems to involve two transition processesnarrow and broad. Furthermore, the fact that the onset transition temperature during heating is lower than that during cooling is also an indication that more than one transition process is involved. On the other hand, the endotherm in the low-temperature region is relatively broad (∼63 °C). At a heating rate of 1 °C/min, the overall heat of transition is 1.6 J/g.…”
Section: Resultsmentioning
confidence: 99%
“…Again, this endothermic process seems to involve two transition processesnarrow and broad. Furthermore, the fact that the onset transition temperature during heating is lower than that during cooling is also an indication that more than one transition process is involved. On the other hand, the endotherm in the low-temperature region is relatively broad (∼63 °C). At a heating rate of 1 °C/min, the overall heat of transition is 1.6 J/g.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that phase behaviors of this series of polymers exhibit an interesting odd−even effect. PEFBPs( n = even) only possess LC phases, while for PEFBPs( n = odd) both LC and crystalline polymorphism have been identified. , Here, we report polymorphous structures and their phase relationships on one of this PEFBP series, of which a 4-cyanobiphenyl mesogen in each side chain is coupled with the aromatic backbone via seven methylene units, PEFBP( n = 7). Compared with those previous studies, , this polymer is the most difficult one to study since the methylene unit number in the side chains is the smallest.…”
Section: Introductionmentioning
confidence: 89%
“…PEFBPs( n = even) only possess LC phases, while for PEFBPs( n = odd) both LC and crystalline polymorphism have been identified. , Here, we report polymorphous structures and their phase relationships on one of this PEFBP series, of which a 4-cyanobiphenyl mesogen in each side chain is coupled with the aromatic backbone via seven methylene units, PEFBP( n = 7). Compared with those previous studies, , this polymer is the most difficult one to study since the methylene unit number in the side chains is the smallest. This results in not only a higher glass transition temperature ( T g ) and other transition temperatures but also a change of the coupling power between the 4-cyanobiphenyls and the backbones.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In order to tune these properties, main-chain LC polymers, comprised of flexible alkylene spacers between rigid and controlled aromatic units, with various chemical structures and molecular architectures for both mesogenic groups and flexible spacers have been designed [1][2][3][4][5][6][7][8][9][10][11]. It is common to tailor LC stabilities by selecting different mesogenic groups, varying the location of the mesogens, and altering the lengths and types of flexible spacers in the LC polymers.…”
Section: Introductionmentioning
confidence: 99%